2021
DOI: 10.1177/2151459321992666
|View full text |Cite
|
Sign up to set email alerts
|

PHILOS Plate Plus Oblique Insertion of Autologous Fibula for 2-Part Proximal Humerus Fractures With Medial Column Disruption: A Retrospective Study

Abstract: Introduction: The aim of this retrospective study was to evaluate the outcomes of older patients with 2-part proximal humerus fractures (PHFs) with medial column disruption stabilized using a proximal humeral internal locking system (PHILOS) plate plus oblique insertion of autologous fibula as a primary procedure. Materials and Methods: Data involving 112 patients (112 shoulders) sustaining 2-part PHFs with medial column disruption treated with PHILOS plate plus oblique insertion of autologous fibula as a prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…The functional outcomes in patients included in the present study experiencing a PHILOS plate plus an allogeneic fibula inserted obliquely were consistent with a recent study 21 of 112 patients with displaced 2-part PHFs experiencing PHILOS plate plus oblique insertion of autologous fibula. Their results showed that the median Constant and ASES scores were 78 (52–95) and 77 (62–96) at the final follow-up, respectively, and the majority of patients were painless with a well-functioning shoulder at the lasted follow-up.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The functional outcomes in patients included in the present study experiencing a PHILOS plate plus an allogeneic fibula inserted obliquely were consistent with a recent study 21 of 112 patients with displaced 2-part PHFs experiencing PHILOS plate plus oblique insertion of autologous fibula. Their results showed that the median Constant and ASES scores were 78 (52–95) and 77 (62–96) at the final follow-up, respectively, and the majority of patients were painless with a well-functioning shoulder at the lasted follow-up.…”
Section: Discussionsupporting
confidence: 90%
“… 26 , 27 In the current study, the rate of the loss of reduction was 4.7% (4/86) and the varus collapse failed to be detected. There is, as far as we know, only 1 prior study involving an allogeneic fibula inserted obliquely, this study 21 evaluating the outcomes according to the Constant and ASES scores and the rate of key orthopaedic complications in 112 patients with 2-part PHFs treated with a PHILOS plate plus oblique insertion of autologous fibula reported that the rate of loss of reduction was 2.6% (3/112), which is consistent with our result. A retrospective study 26 of 36 patients with unstable PHFs with medial column disruption reported a 5.6% rate of varus collapse.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, positive screw angle triggers poor fixation stability and a higher risk of femoral head necrosis, this may root in the limit screw distribution in the femoral head. Specifically, compared to the traditional locking plate, proximal humerus models fixed by the PHILOS plate present better stability [ 13 , 14 ]. Biomechanical research present that the abduction angulation of screw insertion cause a wider screw distribution in the humerus head, which may be an important reason for better angular stability [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the screw insertion angle were an important factor affecting fixation stability [ 11 , 12 ]. Moreover, biomechanical studies on proximal humeral fracture and vertebral burst fracture fixations proved that the cross screw configuration strategy could effectively optimize instant postoperative angular stability [ 13 , 14 ]. The biomechanical significance of cross-angle cannulated screws has also been investigated.…”
Section: Introductionmentioning
confidence: 99%